Investment project controlling with SAP - Esser, Michael (Espresso Tutorials GmbH, 2013)
This book offers practical advice – written by a practitioner for practitioners. It includes SAP screenshots and process flows in order to make the relevant topics visible and applicable. The author makes recommendations related to SAP-PS (Project System) focusing on development projects in which, a new asset is built as a result of the project. It includes SAP screenshots and process flows in order to illustrate the topics. We will coverthe following topics:• SAP ERP functionality for inventment controlling • Concepts, roles and different scenarios• Effective planning and reportingMichael Esser currently serves as a Project Controller at Shell Deutschland Oil GmbH, Cologne. He is responsible for all accounting, controlling, and economics and all other commercial topics related to major investment projects. Prior to his current role, Michael held several key lead auditor and asset accounting roles at KPMG, Lekkerland & Tobacooland, and Warth & Klein Grant Thornton